Pengaruh pendidikan ekonomi keluarga, literasi keuangan, dan gaya hidup terhadap perencanaan keuangan mahasiswa se-Kabupaten Bangkalan - Qomaria, Lailatul; Septiana, Aldila (Jurnal Pendidikan Ekonomi (JUPE), 2024)
aim of this research is to find out how much influence family economic education, financial literacy and lifestyle have on students' financial planning in Bangkalan Regency. This type of research is quantitative research with a population of 100 respondents. Meanwhile, the sample in this study consisted of 60 respondents. The sampling technique was carried out using simple random sampling. Data collection by distributing questionnaires. The results of the research study obtained show that; Family economic education, financial literacy and lifestyle have a significant influence on the financial planning of students throughout Bangkalan Regency. Family economic education has a negative and significant effect on the financial planning of students throughout Bangkalan Regency. Financial literacy has a positive and significant effect on the financial planning behavior of students throughout Bangkalan Regency. Lifestyle has a negative and significant influence on the financial planning of students throughout Bangkalan Regency.